Seasonal dynamics and spatial distribution of aedes albopictus (Diptera - Osório, Hugo C. (2020)
Osório, H. C., Rocha, J., Roquette, R., Guerreiro, N. M., Zé-Zé, L., Amaro, F., Silva, M., & Alves, M. J. (2020). Seasonal dynamics and spatial distribution of aedes albopictus (Diptera: Culicidae) in a temperate region in europe, southern portugal. International Journal of Environmental Research and Public Health, 17(19), 1-11. [7083]. https://doi.org/10.3390/ijerph17197083